2018
DOI: 10.1097/qmh.0000000000000160
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Initiative to Reduce “Out-of-ICU” Cardiopulmonary Arrests in a Tertiary Care Hospital in India: A 2-Year Learning Experience

Abstract: Although MET intervention was successful in significantly reducing "out-of-ICU" Code Blues, focused training of nurses is required for continued quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Every minute in cardiac arrest is valuable. It is found more successful to start CPR in 1.5-2 minutes than in more than 5 minutes [6]. When the maximum time for the CB team to arrive at the scene was asked, most of the participants answered this question correctly but not all of them.…”
Section: Discussionmentioning
confidence: 94%
“…Every minute in cardiac arrest is valuable. It is found more successful to start CPR in 1.5-2 minutes than in more than 5 minutes [6]. When the maximum time for the CB team to arrive at the scene was asked, most of the participants answered this question correctly but not all of them.…”
Section: Discussionmentioning
confidence: 94%
“…1 for additional details of the screening process. Most studies reviewed fit within two categories: they examined the effects of rapid response implementation on patient outcomes ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ), or they described rapid response systems and their associations with patient characteristics and outcomes ( Jung et al., 2022 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch et al., 2019 ; Chan et al., 2016 ; Churpek et al., 2017 ; Jones et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ). Generally, rapid response system implementation studies included scenarios in which the system implemented was the first iteration of its kind ( Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ), was replacing an existing system ( Aitken et al., 2015 ), or added another tier of clinical experience or surveillance to an existing system ( Davis et al., 2015 ; Kawaguchi et al., 2015 ; Pirret et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Broad patterns of what rapid response system components were reported on in included studies were also assessed. A majority of studies (27 of 34) identified what rapid response system triggers were used ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Jung et al., 2022 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ; Bunch et al., 2019 ; Churpek et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ); additionally, a majority of studies (28 of 34) also included at least some details related to member composition of their medical emergency teams ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Jung et al., 2022 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations